A high-performance concrete made from manufactured sand and its preparation method
Patent Information
- Application Number
- CN202611250737.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]为了克服现有技术中机制砂混凝土因机制砂石粉活性较低、界面过渡区结构疏松、拌合物流动性不足以及力学性能和耐久性能难以进一步提升问题,本发明的目的在于提供一种机制砂高性能混凝土及其制备方法
本发明采用硅溶胶与铝溶胶对机制砂石粉进行协同改性,利用硅溶胶粒径小、分散性好的特点,在机制砂石粉表面形成均匀的活性硅质层,同时结合铝溶胶形成稳定的硅铝复合活性层,使机制砂石粉表面活性位点显著增加,增强其对水泥水化产物的诱导成核作用,促进C-S-H凝胶等水化产物在机制砂石粉表面的均匀沉积,从而提高机制砂石粉与水泥浆体之间的界面结合能力,改善界面过渡区结构,减少孔隙及微裂纹的产生,使混凝土内部结构更加致密,提高抗压强度、抗折强度及长期服役稳定性。
Smart Images

Figure CN122977790A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a high-performance concrete made from manufactured sand and its preparation method. Background Technology
[0002] With the increasing depletion of natural river sand resources and the ever-increasing demands for ecological and environmental protection, manufactured sand, due to its wide availability, controllable quality, and high production efficiency, has gradually become an important source of fine aggregate for concrete, and is widely used in infrastructure, prefabricated buildings, bridge engineering, and high-rise buildings. However, manufactured sand is produced by mechanically crushing and shaping rocks, and its particle morphology differs significantly from that of natural river sand. It typically has more angular features, a rougher surface, and a higher stone powder content. While improving the mechanical interlocking effect between aggregate and paste, it also leads to increased water demand, reduced fluidity, and a looser structure in the interfacial transition zone, thus affecting the mechanical properties and durability of concrete.
[0003] Currently, methods to improve the performance of manufactured sand concrete include optimizing the gradation, adding mineral admixtures, adding polycarboxylate superplasticizers, and controlling the stone powder content. Among these, mineral admixtures such as fly ash and granulated blast furnace slag powder can improve the slurry structure, and polycarboxylate superplasticizers can improve the fluidity of the mixture. However, these measures mainly affect the cement paste and have limited impact on improving the surface activity of manufactured sand and the interfacial bonding ability between the manufactured sand and the cement hydration products. Due to its low activity and numerous surface defects, manufactured sand easily forms localized weak areas in the interfacial transition zone, hindering the uniform deposition of hydration products and making it difficult to fully utilize the micro-filling and nucleation effects of the stone powder.
[0004] In recent years, some studies have attempted to modify manufactured sand and gravel powder to improve its interfacial activity and hydration-promoting effect. However, most of these studies use a single silicon source or organic modifier for surface treatment, resulting in problems such as insufficient coating stability, poor modification uniformity, or limited improvement in long-term durability. Meanwhile, a simple, cost-effective, and engineering-applicable technical solution is still lacking regarding how to utilize inorganic active materials to synergistically modify manufactured sand and gravel powder, improve its surface activity, promote the uniform generation of cement hydration products, and further optimize the structure of the concrete interfacial transition zone.
[0005] Therefore, developing a high-performance concrete made from manufactured sand and its preparation method, which improves the interfacial bonding between manufactured sand and cement matrix through efficient synergistic modification of manufactured sand powder, thereby improving the workability, mechanical properties and durability of concrete, is of great significance for promoting the high-value utilization of manufactured sand resources and the development of high-performance concrete. Summary of the Invention
[0006] To overcome the problems of low activity of manufactured sand powder, loose interfacial transition zone structure, insufficient fluidity of the mixture, and difficulty in further improving mechanical and durability properties in existing manufactured sand concrete technologies, this invention aims to provide a high-performance manufactured sand concrete and its preparation method. This invention uses silica sol and alumina sol to synergistically modify manufactured sand powder with a particle size of 0.005–0.075 mm, forming a stable inorganic active layer on its surface. This active layer is then compounded with ordinary silicate cement, manufactured sand, crushed stone, mineral admixtures, betaine, and polycarboxylate superplasticizer to prepare high-performance manufactured sand concrete. This improves the interfacial bonding performance between the manufactured sand powder and cement paste, and optimizes the internal microstructure of the concrete. Compared with existing technologies, this invention, through the synergistic modification of manufactured sand powder with silica sol and alumina sol, improves the workability, mechanical properties, and durability of manufactured sand concrete, demonstrating significant engineering application value.
[0007] The objective of this invention can be achieved through the following technical solutions: A high-performance concrete using manufactured sand comprises the following raw materials in parts by weight: 300-450 parts ordinary Portland cement; 650-900 parts manufactured sand; 850-1200 parts crushed stone; 50-180 parts mineral admixtures; 10-60 parts silica sol-alumina sol synergistic modified manufactured sand powder; 0.05-1.5 parts betaine; 2-8 parts polycarboxylate superplasticizer; and 120-220 parts water. The silica sol-alumina sol synergistic modified manufactured sand powder is obtained by impregnating and drying manufactured sand powder with silica sol and alumina sol. The mineral admixtures are one or both of fly ash and granulated blast furnace slag powder. The particle size of the manufactured sand is 0.15-4.75 mm.
[0008] Optionally, the silica sol-alumina sol synergistic modification of manufactured sand and gravel powder comprises the following raw materials in parts by weight: 100 parts manufactured sand and gravel powder; 5-20 parts silica sol; 3-15 parts alumina sol; 80-250 parts deionized water; and the particle size of the manufactured sand and gravel powder is 0.005-0.075 mm.
[0009] Optionally, the preparation method of silica sol-alumina sol synergistic modification of manufactured sand and gravel powder includes the following steps: (1) Mix silica sol, aluminum sol and deionized water evenly to prepare silica-alumina composite sol; (2) The manufactured sand and gravel powder is added to the silicon-aluminum composite sol for impregnation treatment to obtain a modified slurry; (3) The modified slurry is dried, crushed and sieved to obtain the silica sol-alumina sol synergistic modified mechanism sand and gravel powder.
[0010] Optionally, the reaction conditions in step (1) are a stirring temperature of 20-35°C, a stirring time of 20-40 min, and a stirring speed of 300-600 r / min.
[0011] Optionally, the reaction conditions for step (2) are: impregnation temperature of 25-40°C, impregnation time of 2-6 hours, and stirring speed of 200-500 r / min.
[0012] Optionally, the reaction conditions in step (3) are a drying temperature of 80-100℃, a drying time of 6-10h, and pulverization followed by passing through a 200-325 mesh sieve.
[0013] Optionally, the polycarboxylate superplasticizer is composed of polycarboxylate superplasticizer mother liquor, polyether modified slump retainer, organosilicon defoamer and sodium gluconate in a mass ratio of 100:(3-8):(0.05-0.30):(0.5-2).
[0014] Optionally, a method for preparing high-performance concrete using manufactured sand includes the following steps: S1, ordinary silicate cement, manufactured sand, crushed stone, mineral admixtures and silica sol-alumina sol synergistic modification of manufactured sand and stone powder are mixed evenly to obtain dry mix; S2, after mixing betaine, water and polycarboxylate superplasticizer evenly, add them to the dry mixture and stir evenly to obtain concrete mixture; S3, the concrete mixture is poured into shape, compacted and cured to obtain the high-performance concrete made from manufactured sand.
[0015] Optionally, the reaction conditions for step S1 are: dry mixing time of 2-5 min and stirring speed of 30-60 r / min; the reaction conditions for step S2 are: premixing betaine, water and polycarboxylate superplasticizer for 3-8 min, then adding them to the dry mixture and wet mixing for 3-6 min, with a stirring speed of 40-80 r / min.
[0016] Optionally, the reaction conditions for step S3 are: compaction time of 20-60 seconds, demolding after standing for 12-24 hours, and curing for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 95%.
[0017] The beneficial effects of this invention are: This invention employs silica sol and alumina sol to synergistically modify manufactured sand and gravel powder. Utilizing the small particle size and good dispersibility of silica sol, a uniform active silica layer is formed on the surface of the manufactured sand and gravel powder. Simultaneously, combined with alumina sol, a stable silica-alumina composite active layer is formed. This significantly increases the number of active sites on the surface of the manufactured sand and gravel powder, enhancing its induction of nucleation of cement hydration products. It promotes the uniform deposition of hydration products such as CSH gel on the surface of the manufactured sand and gravel powder, thereby improving the interfacial bonding between the manufactured sand and gravel powder and cement paste, improving the structure of the interfacial transition zone, reducing the generation of pores and microcracks, making the internal structure of concrete denser, and improving compressive strength, flexural strength, and long-term service stability.
[0018] This invention, based on the synergistic modification of manufactured sand and gravel powder by silica sol and alumina sol, introduces the synergistic effect of betaine and polycarboxylate superplasticizer. Betaine can improve the hydration environment on the surface of cement particles and modified manufactured sand and gravel powder, reduce the unfavorable agglomeration between particles in the mixing system, and form a synergistic dispersion effect with polycarboxylate superplasticizer, thereby improving the ability of the slurry to coat manufactured sand particles. It can maintain good fluidity and workability while ensuring a low water-cement ratio, and at the same time reduce the slump loss caused by the adsorption of admixtures by manufactured sand and gravel powder, so that the concrete has more stable workability.
[0019] This invention uses silica sol and alumina sol to synergistically modify manufactured sand and gravel powder to replace traditional untreated stone powder. This not only fully utilizes the micro-filling and activity effects of manufactured sand and gravel powder, but also improves the comprehensive utilization rate of stone powder resources. It transforms stone powder from an inert filler into a functional component with certain activity, forming a synergistic effect with mineral admixtures. This further optimizes the pore structure of concrete, improves impermeability, freeze-thaw resistance, and durability. While ensuring excellent comprehensive performance, it does not require complex equipment or special processes. The preparation method is simple and cost-effective, making it suitable for the large-scale production and engineering application of high-performance manufactured sand concrete. Attached Figure Description
[0020] The invention will now be further described with reference to the accompanying drawings.
[0021] Figure 1 A comparison chart of slump and slump retention performance test results for samples with different proportions. Detailed Implementation
[0022] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.
[0023] Example 1: The purpose of this example is to verify the effect of the synergistic modification of manufactured sand powder with silica sol-alumina sol, betaine, polycarboxylate superplasticizer and mineral admixture on the workability, mechanical properties and durability of manufactured sand concrete when each component adopts the lower limit ratio within the scope of the claims and the corresponding lower limit process conditions are adopted.
[0024] S1. Preparation of synergistic modification of manufactured sand and gravel powder using silica sol and alumina sol Weigh out 100 parts of manufactured sand and gravel powder, 5 parts of silica sol, 3 parts of alumina sol, and 80 parts of deionized water. First, mix the silica sol, alumina sol, and deionized water evenly and stir for 20 minutes at a stirring temperature of 20℃ and a stirring speed of 300 r / min to obtain a silica-alumina composite sol. Then, add the manufactured sand and gravel powder to the silica-alumina composite sol for impregnation treatment at a stirring temperature of 25℃ and a stirring speed of 200 r / min for 2 hours to obtain a modified slurry. Finally, dry the obtained modified slurry at 80℃ for 6 hours, pulverize it after drying, and pass it through a 200-mesh sieve to obtain silica sol-alumina sol synergistic modified manufactured sand and gravel powder. S2, High-performance concrete mixing with manufactured sand Weigh out 300 parts of ordinary Portland cement, 650 parts of manufactured sand, 850 parts of crushed stone, 50 parts of mineral admixture, and 10 parts of the silica sol-alumina sol synergistic modified manufactured sand and stone powder prepared above, and add them to a mixer. Dry mix for 2 minutes at a mixing speed of 30 r / min to obtain a dry mix. The mineral admixture is fly ash. Separately weigh out 0.05 parts of betaine, 120 parts of water, and 2 parts of polycarboxylate superplasticizer. The polycarboxylate superplasticizer is composed of polycarboxylate superplasticizer mother liquor, polyether modified slump retainer, organosilicon defoamer, and sodium gluconate mixed in a mass ratio of 100:3:0.05:0.5. Mix the betaine, water, and polycarboxylate superplasticizer, and premix for 3 minutes at 40 r / min to form an admixture solution. Then add the admixture solution to the dry mix and wet mix for 3 minutes at 40 r / min to obtain a homogeneous concrete mixture. S3, Pouring and Curing The obtained concrete mixture was poured into a test mold, compacted on a vibrating table for 20 seconds, left to stand for 12 hours, and then demolded. It was then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days to obtain high-performance concrete made from manufactured sand.
[0025] Example 2: The purpose of this example is to verify the synergistic effect of silica sol-alumina sol synergistic modification of manufactured sand powder with betaine, polycarboxylate superplasticizer and mineral admixtures on improving the workability, mechanical properties and durability of manufactured sand concrete when the components are in the intermediate proportions defined in the claims and appropriate process conditions are adopted. This example is the preferred embodiment of the present invention.
[0026] S1. Preparation of synergistic modification of manufactured sand and gravel powder using silica sol and alumina sol Weigh out 100 parts of manufactured sand powder, 12.5 parts of silica sol, 9 parts of alumina sol, and 165 parts of deionized water. First, mix the silica sol, alumina sol, and deionized water, and stir for 30 minutes at a stirring temperature of 28℃ and a stirring speed of 450 r / min to obtain a silica-alumina composite sol. Then, add the manufactured sand powder to the silica-alumina composite sol and impregnate for 4 hours at an impregnation temperature of 32℃ and a stirring speed of 350 r / min to obtain a modified slurry. Finally, dry the modified slurry at 90℃ for 8 hours, pulverize it after drying, and pass it through a 260-mesh sieve to obtain silica sol-alumina sol synergistic modified manufactured sand powder. S2, High-performance concrete mixing with manufactured sand Weigh out 375 parts of ordinary silicate cement, 775 parts of manufactured sand, 1025 parts of crushed stone, 115 parts of mineral admixture, and 35 parts of the silica sol-alumina sol synergistic modified manufactured sand powder prepared above, and add them to a mixer. Dry mix for 3.5 minutes at a mixing speed of 45 r / min to obtain a dry mix. The mineral admixture consists of fly ash and granulated blast furnace slag powder in a mass ratio of 1:1. Separately weigh out 0.75 parts of betaine, 170 parts of water, and 5 parts of polycarboxylate superplasticizer. The polycarboxylate superplasticizer is composed of polycarboxylate superplasticizer mother liquor, polyether modified slump retainer, organosilicon defoamer, and sodium gluconate mixed in a mass ratio of 100:5.5:0.15:1.2. Betaine, water, and polycarboxylate superplasticizer are mixed and premixed at 60 r / min for 5 min to form an admixture solution. The admixture solution is then added to the dry mix and wet-mixed at 60 r / min for 4.5 min to uniformly coat the manufactured sand and coarse aggregate, resulting in a homogeneous concrete mixture. S3, Pouring and Curing The obtained concrete mixture was poured into a test mold, compacted on a vibrating table for 40 seconds, allowed to stand for 18 hours, and then demolded. It was then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days to obtain high-performance concrete made from manufactured sand.
[0027] Example 3: The purpose of this example is to verify the effect of the synergistic effect of silica sol-alumina sol synergistic modification of manufactured sand and gravel powder with betaine, polycarboxylate superplasticizer and mineral admixture on the comprehensive performance of manufactured sand concrete when each component adopts the upper limit ratio within the scope of the claims and adopts the corresponding upper limit process conditions. It further verifies that the technical solution of the present invention still has good applicability and stability under higher dosage conditions.
[0028] S1. Preparation of synergistic modification of manufactured sand and gravel powder using silica sol and alumina sol Weigh out 100 parts of manufactured sand powder, 20 parts of silica sol, 15 parts of alumina sol, and 250 parts of deionized water. First, mix the silica sol, alumina sol, and deionized water, and stir for 40 minutes at a stirring temperature of 35℃ and a stirring speed of 600 r / min to obtain a silica-alumina composite sol. Then, add the manufactured sand powder to the silica-alumina composite sol and impregnate for 6 hours at an impregnation temperature of 40℃ and a stirring speed of 500 r / min to obtain a modified slurry. Finally, dry the modified slurry at 100℃ for 10 hours, pulverize it after drying, and pass it through a 325-mesh sieve to obtain silica sol-alumina sol synergistic modified manufactured sand powder. S2, High-performance concrete mixing with manufactured sand Weigh out 450 parts of ordinary silicate cement, 900 parts of manufactured sand, 1200 parts of crushed stone, 180 parts of mineral admixture, and 60 parts of the silica sol-alumina sol synergistic modified manufactured sand powder prepared above, and add them to a mixer. Dry mix for 5 minutes at a mixing speed of 60 r / min to obtain a dry mix. The mineral admixture consists of fly ash and granulated blast furnace slag powder in a mass ratio of 1:1. Separately weigh out 1.5 parts of betaine, 220 parts of water, and 8 parts of polycarboxylate superplasticizer. The polycarboxylate superplasticizer is composed of polycarboxylate superplasticizer mother liquor, polyether modified slump retainer, organosilicon defoamer, and sodium gluconate mixed in a mass ratio of 100:8:0.30:2. Betaine, water, and polycarboxylate superplasticizer are mixed and premixed at 80 r / min for 8 min to form an admixture solution. The admixture solution is then added to the dry mix and wet-mixed at 80 r / min for 6 min to ensure that the paste fully coats each component and obtains a homogeneous concrete mixture. S3, Pouring and Curing The obtained concrete mixture was poured into a test mold, compacted on a vibrating table for 60 seconds, allowed to stand for 24 hours, and then demolded. It was then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days to obtain high-performance concrete made from manufactured sand.
[0029] Comparative Example 1: This comparative example is used to verify the comprehensive performance of concrete prepared directly using ordinary manufactured sand that has not been modified and contains manufactured sand powder, and to compare it with the high-performance concrete prepared by the present invention using silica sol-alumina sol synergistic modification of manufactured sand powder.
[0030] S1. Raw material preparation Manufactured sand from the same lithological source as in Example 2 was selected. The particle size of the manufactured sand was 0.15–4.75 mm. The manufactured sand retained the original manufactured sand powder generated during the production process, without separation, silica sol modification, alumina sol modification, or other surface modification treatments. The particle size of the manufactured sand powder in the manufactured sand was 0.005–0.075 mm. S2, Mixing of manufactured sand concrete Weigh out 375 parts of ordinary Portland cement, 810 parts of the above-mentioned manufactured sand containing manufactured sand and gravel powder, 1025 parts of crushed stone, and 115 parts of mineral admixtures and put them into a mixer. Dry mix for 3.5 minutes at a mixing speed of 45 r / min to obtain a dry mix. The mineral admixture is composed of fly ash and granulated blast furnace slag powder mixed in a mass ratio of 1:1. Separately weigh out 170 parts of water and 5 parts of ordinary polycarboxylate superplasticizer. Mix the water and ordinary polycarboxylate superplasticizer evenly and then add them to the dry mix. Wet mix for 4.5 minutes at a speed of 60 r / min to obtain a manufactured sand concrete mixture. S3, Pouring and Curing The obtained manufactured sand concrete mixture was poured into a test mold, compacted by a vibrating table for 40 seconds, and then demolded after standing for 18 hours. It was then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days to obtain the comparative example 1 sample.
[0031] Comparative Example 2: This comparative example is used to simulate ordinary concrete prepared using natural river sand as fine aggregate, in order to evaluate the workability, mechanical properties and durability of the high-performance concrete made from manufactured sand of the present invention after replacing natural river sand concrete.
[0032] S1. Raw material preparation Natural river sand is selected as the fine aggregate, and the particle size of the natural river sand is 0.15–4.75 mm. Before use, the natural river sand is screened to remove obvious impurities and is not subjected to silica sol, alumina sol, or other surface modification treatments. S2, River Sand Concrete Mixing Weigh out 375 parts of ordinary Portland cement, 810 parts of natural river sand, 1025 parts of crushed stone, and 115 parts of mineral admixtures and put them into a mixer. Dry mix for 3.5 minutes at a mixing speed of 45 r / min to obtain a dry mix. The mineral admixtures are composed of fly ash and granulated blast furnace slag powder mixed in a mass ratio of 1:1. Separately weigh out 170 parts of water and 5 parts of ordinary polycarboxylate superplasticizer. Mix the water and ordinary polycarboxylate superplasticizer evenly and then add them to the dry mix. Wet mix for 4.5 minutes at a speed of 60 r / min to obtain a river sand concrete mixture. S3, Pouring and Curing The obtained river sand concrete mixture was poured into a test mold, compacted with a vibrating table for 40 seconds, and then demolded after standing for 18 hours. It was then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days to obtain the comparative example 2 sample.
[0033] Performance testing: 1. Slump and slump retention performance test The tests were conducted according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T50080). After thoroughly mixing the fresh concrete prepared in Examples 1-3 and Comparative Examples 1-2, slump tests were immediately performed, and the initial slump was recorded. Subsequently, the concrete mixture was placed in an environment at (20±2)℃ for 60 minutes, and the slump was measured again, recording the slump value after 60 minutes to evaluate the workability and slump retention capacity of the concrete mixture. Each group of samples was tested in triplicate, and the average value was taken as the final test result.
[0034] 2. Compressive strength test Tests were conducted according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T50081). The concrete obtained in Examples 1-3 and Comparative Examples 1-2 were cast into 100mm × 100mm × 100mm cube specimens. After curing under standard conditions (20±2℃, relative humidity ≥95%) for 28 days, the 28-day compressive strength of the specimens was determined using a compression testing machine. Three parallel specimens were prepared for each group, and the average value was used as the final test result to evaluate the mechanical properties of the concrete.
[0035] 3. Chloride ion penetration resistance test The rapid chloride ion migration test method was performed according to the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB / T50082). Concrete specimens cured for 28 days were processed to the specified dimensions, vacuum-saturated with water, and then placed in a chloride ion migration test apparatus. The test was conducted under specified voltage conditions to determine the chloride ion migration coefficient (RCM value) of the concrete. Each group of samples was tested in triplicate, and the average value was taken as the final test result. The lower the chloride ion migration coefficient, the denser the internal structure of the concrete, and the better its impermeability and durability.
[0036] 4. Antifreeze performance test Rapid freeze-thaw cycle tests were conducted according to the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB / T50082). Concrete specimens cured for 28 days were placed in a freeze-thaw testing machine and subjected to 300 rapid freeze-thaw cycles under the specified freeze-thaw regime. After the test, the retention rate of the relative dynamic modulus of elasticity and the mass loss rate of the specimens were measured, with the retention rate of the relative dynamic modulus of elasticity used as the main evaluation index. Each group of samples was tested in triplicate, and the average value was taken as the final test result. A higher retention rate of the relative dynamic modulus of elasticity and a lower mass loss rate indicate better freeze-thaw durability of the concrete.
[0037] Table 1. Performance test results of the examples and comparative examples.
[0038] As shown in Table 1, the high-performance manufactured sand concrete prepared in Examples 1-3 significantly outperformed Comparative Examples 1 and 2 in terms of workability, mechanical properties, and durability, with Example 2 exhibiting the best overall performance. This indicates that the synergistic modification of manufactured sand powder with silica sol and alumina sol has a good synergistic reinforcing effect with betaine, which can significantly improve the interfacial structure and overall service performance of manufactured sand concrete.
[0039] In terms of workability, the initial slump of Examples 1-3 reached 208 mm, 222 mm, and 216 mm, respectively, and the slump maintained at 183 mm, 203 mm, and 194 mm at 60 minutes, respectively, all significantly higher than Comparative Example 1 and Comparative Example 2. Among them, Example 2 had the highest initial slump and the best slump retention performance, indicating that the synergistic modification of manufactured sand and gravel powder with silica sol and alumina sol can effectively reduce the adsorption of polycarboxylate superplasticizer by manufactured sand and gravel powder and improve the uniformity of paste dispersion. At the same time, betaine further enhanced the dispersion effect of the superplasticizer, reduced the cohesive resistance of the mixture, and made the concrete have better fluidity and slump retention ability. In contrast, Comparative Example 1 used unmodified manufactured sand and gravel powder, which had a large specific surface area and strong water absorption capacity, resulting in a significant decrease in workability. Comparative Example 2 lacked the synergistic effect of betaine, and its slump retention performance was also reduced.
[0040] From a mechanical property perspective, the 28-day compressive strengths of Examples 1-3 reached 64.8 MPa, 70.3 MPa, and 68.2 MPa, respectively, all higher than the 56.7 MPa of Comparative Example 1 and 60.4 MPa of Comparative Example 2, with Example 2 showing the most significant improvement. This indicates that after silica sol and alumina sol form a stable active silica-alumina layer on the surface of manufactured sand and gravel powder, they can promote the generation of cement hydration products and enhance the interfacial bonding between manufactured sand and cement paste. Simultaneously, the modified stone powder exerts a micro-filling effect and a nucleation effect, further refining the internal pores of the concrete and making the interfacial transition zone denser, thereby significantly improving the compressive strength of the concrete. Although the dosage of each component in Example 3 was further increased, the synergistic reinforcing effect tended to saturate due to the increased paste viscosity, resulting in a slightly lower overall strength than Example 2.
[0041] In terms of chloride ion penetration resistance, the chloride ion migration coefficients of Examples 1-3 were 6.05×10⁻¹² m² / s, 4.58×10⁻¹² m² / s, and 5.02×10⁻¹² m² / s, respectively, all significantly lower than those of Comparative Example 1 and Comparative Example 2. Among them, Example 2 exhibited the lowest chloride ion migration coefficient, indicating the formation of a more continuous and dense microstructure within the concrete. The reason for this is that the synergistic modification of the manufactured sand and gravel powder with silica sol and alumina sol not only improved the surface activity of the stone powder but also promoted the uniform deposition of hydrated gel in the interfacial region, effectively reducing the number of capillary pores and interconnected pores, thereby significantly improving the concrete's resistance to chloride ion erosion and enhancing its long-term durability.
[0042] In terms of freeze-thaw resistance, after 300 rapid freeze-thaw cycles, the relative dynamic modulus of elasticity retention rates of Examples 1-3 reached 92.1%, 96.3%, and 94.8%, respectively, all significantly higher than 84.6% of Comparative Example 1 and 88.5% of Comparative Example 2, with Example 2 showing the highest retention rate. This indicates that the concrete prepared by this invention has a more stable internal structure, effectively inhibiting the generation and propagation of microcracks during freeze-thaw cycles and reducing the degree of freeze-thaw damage. In particular, the synergistic effect of silica sol-alumina sol modified aggregate powder and betaine strengthens the bond between the paste and aggregate interface, reducing moisture migration and frost heave damage, thus significantly improving the freeze-thaw durability of the concrete.
[0043] The synergistic modification of manufactured sand powder using silica sol-alumina sol, combined with the combined action of betaine and polycarboxylate superplasticizer, effectively improves the fluidity, slump retention, compressive strength, chloride ion penetration resistance, and freeze-thaw resistance of manufactured sand concrete. In Example 2, with a medium mix ratio, the synergistic effect among the components is most pronounced, resulting in the densest internal structure of the concrete and optimal overall performance. Examples 1 and 3 are also superior to the comparative examples, fully demonstrating the significant technical effects and excellent engineering application value of this invention.
Claims
1. A type of high-performance concrete made from manufactured sand, characterized in that, The raw materials include the following parts by weight: 300-450 parts ordinary silicate cement; 650-900 parts manufactured sand; 850-1200 parts crushed stone; 50-180 parts mineral admixtures; 10-60 parts silica sol-alumina sol synergistic modified manufactured sand powder; 0.05-1.5 parts betaine; 2-8 parts polycarboxylate superplasticizer; and 120-220 parts water. The silica sol-alumina sol synergistic modified manufactured sand powder is obtained by synergistic impregnation and drying of manufactured sand powder with silica sol and alumina sol. The mineral admixtures are one or both of fly ash and granulated blast furnace slag powder. The particle size of the manufactured sand is 0.15-4.75 mm.
2. The high-performance concrete made from manufactured sand according to claim 1, characterized in that, The silica sol-alumina sol synergistic modification of the manufactured sand and gravel powder comprises the following raw materials in parts by weight: 100 parts manufactured sand and gravel powder; 5-20 parts silica sol; 3-15 parts alumina sol; 80-250 parts deionized water; and the particle size of the manufactured sand and gravel powder is 0.005-0.075 mm.
3. A high-performance concrete made from manufactured sand according to claim 1 or 2, characterized in that, The preparation method of the silica sol-alumina sol synergistic modification of the manufactured sand and gravel powder includes the following steps: (1) Mix silica sol, aluminum sol and deionized water evenly to prepare silica-alumina composite sol; (2) The manufactured sand and gravel powder is added to the silicon-aluminum composite sol for impregnation treatment to obtain a modified slurry; (3) The modified slurry is dried, crushed and sieved to obtain the silica sol-alumina sol synergistic modified mechanism sand and gravel powder.
4. The high-performance concrete made from manufactured sand according to claim 3, characterized in that, The reaction conditions for step (1) are: stirring temperature 20-35℃, stirring time 20-40min, and stirring speed 300-600r / min.
5. The high-performance concrete made from manufactured sand according to claim 3, characterized in that, The reaction conditions for step (2) are: immersion temperature 25-40℃, immersion time 2-6h, and stirring speed 200-500r / min.
6. The high-performance concrete made from manufactured sand according to claim 3, characterized in that, The reaction conditions for step (3) are a drying temperature of 80-100℃, a drying time of 6-10h, and pulverization followed by passing through a 200-325 mesh sieve.
7. The high-performance concrete made from manufactured sand according to claim 1, characterized in that, The polycarboxylate superplasticizer is composed of polycarboxylate superplasticizer mother liquor, polyether modified slump retainer, organosilicon defoamer and sodium gluconate in a mass ratio of 100:(3-8):(0.05-0.30):(0.5-2).
8. A method for preparing high-performance concrete using manufactured sand, characterized in that, The preparation method includes the following steps: S1, ordinary silicate cement, manufactured sand, crushed stone, mineral admixtures and silica sol-alumina sol synergistic modification of manufactured sand and stone powder are mixed evenly to obtain dry mix; S2, after mixing betaine, water and polycarboxylate superplasticizer evenly, add them to the dry mixture and stir evenly to obtain concrete mixture; S3, the concrete mixture is poured into shape, compacted and cured to obtain the high-performance concrete made from manufactured sand.
9. The method for preparing high-performance concrete using manufactured sand according to claim 8, characterized in that, The reaction conditions for step S1 are: dry mixing time of 2-5 min and stirring speed of 30-60 r / min; the reaction conditions for step S2 are: premixing betaine, water and polycarboxylate superplasticizer for 3-8 min, then adding them to the dry mixture and wet mixing for 3-6 min, with a stirring speed of 40-80 r / min.
10. The method for preparing high-performance concrete using manufactured sand according to claim 8, characterized in that, The reaction conditions for step S3 are: compaction time of 20-60 seconds, standing for 12-24 hours, demolding, and curing for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 95%.